THE APPLICATION OF THE PRINCIPLE OF COHERENCE IN AL-HASHR: PERSPECTIVE OF QAWAID TAFSIR BY KHOLID BIN UTSMAN AL-SABT - Muhammad Faisal Purnomosidi; Andri Nirwana AN; Qoree Butlam (Profetika: Jurnal Studi Islam, 2024)
Qawaid Tafsir by Khalid bin Uthman as Sabt is a book that formulates the sciences of exegesis into the form of rules, including reasonable calm in the Qur'an, he formulated three rules about reasonableness. First, most verses close with al-asma' al-husna to show that the message of the verse relates to these great names. Second, two adjacent verses or sentences, clearly or unclearly related, must have a unifying facet. Third, the general steps to find plausibility between verses in the Qur'an are to look for the surah, make provisional conclusions, analyze the provisional conclusions, and draw up the conclusion. This research is qualitative. Primary data sources are QS Al Hasyar, and secondary sources are the books "Reasonable Discourse of the Qur'an in Tafsir Al-Misbah" by Hasani Ahmad Said and books on 'Tulum al-Qur'an related to munasabah. The data collection method is carried out by (1) collecting verses that contain plausibility, (2) categorizing reasonable verses, and (2) analyzing through Qaedah Tafsir Khalid bin Usman As Sabat. Based on the analysis conducted, the study concluded that the author did that rule number 196 in the book of award tafsir is applied to verses 1, 6, 10, 18, 22, and 24. For rule 197 applied to verses 2,3,4,5,7,8,9,11,12,13,14,15,1617,19,20,21, and 24. While the 198th rule does not apply to the verse in Surat al Hashr